Pengaruh Penerapan Media Pembelajaran Game Edukasi SIMARUN terhadap Kemampuan Siswa Dalam Memahami Materi di SMP N 11 Muaro Jambi - faguma; Sariani, Dona (Civic Education Perspective Journal, 2024)
The purpose of this study was to determine whether there was a significant effect of the application of variable X in this case the Simarun educational game on variable y, namely students' ability to understand the material. This study adopted an experimental quantitative research design. This study was carried out in 3 stages, namely the pre-field stage in January 2022, the field work stage in April 2022 to May 2022 and the data analysis stage in June 2022. The sample in this study was class VIII B and VIII D totaling 54 students as representatives of the total population of class VIII students. The results of this study found that the average value of the experimental class or the class that implemented the simarun educational game was 6.52 while the control class that used ordinary learning media had an average value of 2.85 so it can be concluded that the average experimental value of 3.67 is greater than the control class, meaning that the increase in value after the implementation of the simarun educational game in the experimental class is greater than the control class and based on the calculation of the paired sample t-test using SPSS21, sig (2 tailed) = 0.00 means that it is less than 0.05, so it can be concluded that the data is significant or there is a significant difference in the increase in scores between the experimental class and the control class. This study has results that can be concluded, namely after the implementation of the simarun learning media in the experimental class or class VIII B, it can be concluded that there is an effect of the application of the simarun educational game on students' ability to understand PPKn material in class VIII of SMPN 11 Muaro Jambi